Quotes, Prices, and Estimates in a Laboratory Market - Bloomfield, Robert (Journal of Finance, 1996)
This study examines the behavior of laboratory markets in which two uninformed market makers compete to trade with heterogeneously informed investors. The data provide three main results. First, market makers set quotes to protect against adverse selection and to control inventory. Second, when investors are less well-informed, their trades are less reliable measures of their information, and market makers respond to those trades with greater skepticism. Third, errors in market makers' reactions to trades cause the time-series behavior of quotes and prices to depend on the information environment in ways beyond those captured in extant theory.